2017
DOI: 10.19102/icrm.2017.080803
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Electronic Personal Health Records to Improve Medication Adherence and Patient Engagement: A Randomized Study of Non-valvular Atrial Fibrillation Patients

Abstract: ABSTRACT. Embolic stroke is a major complication of atrial fibrillation (AF) that frequently results in disability or death. The administration of oral anticoagulation can reduce stroke risk in AF patients; however, medication non-adherence can eliminate this benefit. To date, reported patient adherence rates to oral anticoagulation regimens vary. The objective of the current study was to examine the impact of medication-specific education delivered via a personal health record (PHR) system on medication adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…This re‐education approach is not new; a previous study demonstrated that a complex education intervention increased AF patients' knowledge of their condition at both 12 and 24 months (Taitel, Mu, Gooptu, & Lou, 2017). In our own pilot work, we found that both AF knowledge and OAC adherence could be increased by the use of tailored digital education through the electronic health record (Chen et al, 2017). Though participants in this study suggested tailoring precise timing to the individual for maximum effectiveness, many agreed it would be helpful to initially receive more frequent follow‐ups for a short period of time immediately after diagnosis (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This re‐education approach is not new; a previous study demonstrated that a complex education intervention increased AF patients' knowledge of their condition at both 12 and 24 months (Taitel, Mu, Gooptu, & Lou, 2017). In our own pilot work, we found that both AF knowledge and OAC adherence could be increased by the use of tailored digital education through the electronic health record (Chen et al, 2017). Though participants in this study suggested tailoring precise timing to the individual for maximum effectiveness, many agreed it would be helpful to initially receive more frequent follow‐ups for a short period of time immediately after diagnosis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…They generally rated their computer literacy as adequate, but the age group most affected by AF (65+) contains a wide range of technological capabilities. However, prior research has demonstrated effectiveness in using a computerized PHR to deliver messaging to AF patients that increases knowledge and adherence (Chen et al, 2017), as well as that, although older patients rate their computer literacy lower, they may be more likely to actively use electronic methods of monitoring their health once they are introduced and trained on how to use them (Toscos et al, 2016). Our participants' current device use (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent screening and review of titles and abstracts for inclusion eligibility were conducted by 2 reviewers. Authors were contacted to obtain information on studies, including 2 with only abstract proceedings available at the time of search 15,19 and another for which additional information on mean knowledge and TTR values was required. 20 Because this review was an update of the review conducted by Wong et al, 9 references before 2012 were excluded from the screening process.…”
Section: Medline Embase and Cochrane Central Register Of Controlledmentioning
confidence: 99%
“…23 Authors were contacted to obtain data identified from abstract screening; however, the data were not published at the time of the analysis. 19 Two authors were contacted to provide means and SDs for knowledge scores, and data were obtained for 1 study 15 but not the other. 20 Heterogeneity of the eligible studies was assessed using the x 2 test, with significance at P , .10, and the I 2 statistic, 11 which was the primary measure used to assess degree of heterogeneity.…”
Section: Medline Embase and Cochrane Central Register Of Controlledmentioning
confidence: 99%